"Let's Pick Him!": Ratings of Skill Level on the Basis of in-Game Playing Behaviour in Bantam League Junior ICE Hockey. Issue 4 (December 2013) - Tromp, E. J. Yvonne; Pepping, Gert-Jan; Lyons, Jim; Elferink-Gemser, Marije T.; Visscher, Chris
Rating a player's skill level is an essential task for coaches to select the players with greatest potential to reach the top and to further be able to adjust the training program to the skill level of the player in order to most optimally facilitate the player's learning and performance. However, limited research exists on how they do this. This study examined the association between in-game playing behaviours and observers' ratings of skill level. Three observers rated 71 junior ice hockey players (House League Level, Bantam Division in Canada). Results revealed that players were more often rated high skilled when they executed a greater numbers of actions, of which relatively more shots and carries compared to passes, and when they were involved in the play more often (p < .05). Conversely, players were rated more often low skilled when they executed fewer actions, of which relatively more passes, and when they were involved in the play less often (p < .05). The in-game playing behaviours appeared to be used as information sources for player ratings. The results presented highlight the need for further research on the sources of information used by coaches as it will increase awareness about their coaching's process with regard to player selection and player development.